Correlation of Coordination Abilities, Physical Qualities and Mental Processes of Football Players - Polevoy G.G. (Pakistan Journal of Medical & Health Sciences, 2022)
The aim set out in Article research is to find new of methodical approaches to improve the methods of development of coordination abilities of young players. Despite the proven efficacy of the differentiated approach in the preparation of sports reserve, no data found, taking into account the typological features of display properties of the nervous system of children involved in football. Methods and techniques: We used statistical methods to determine the validity and reliability of the results of scientific research. Statistical analysis was performed using a personal computer Pentium- 4 and using the Microsoft standard statistical software package Excel 2007. Correlation analysis was performed using the program Bio Stat 2016. Results: Identified and synthesized a new classification of specific coordination abilities in terms of their impact on mental processes of young football players. The new data that expand and deepen the modern theory and methodology of football with new knowledge about the coordination abilities, peculiarities of the relationship indicators conditional abilities and mental processes with the indicators of specific coordination abilities of the players with strong and weak nervous system. Scientific novelty: Demonstrated prospect for a differentiated approach based on a typology. The features of the relationship of coordination abilities indicators with indicators of conditional abilities and mental processes of the players of 11-12 years with a "strong" and "weak" the nervous system. Defined "leading" and "additional" specific types of coordination abilities in different groups of players. Practical significance: Accounting data obtained as a result of the correlation analysis, in the training process of young players can provide a significant increase in the efficiency of the development process -specific coordination abilities, level of mastery of the technical and tactical methods and competitive performance, as well as improve the performance of the mental processes of children involved in football.